Pengaruh Kualitas Manajer Pajak Terhadap Penghindaran Pajak Dengan Etika Machiavellian Sebagai Pemediasi - Estralita Trisnawati; Roy Sembel; Juniati Gunawan; Waluyo (Jurnal Ekonomi, 2017)
This study aims to examine the effect of tax managers' quality on tax avoidance of manufacturing industry firms listed on the Indonesia Stock Exchange with machiavellian ethics as intervening. Using path analysis model with WarpPLS 5.0. This study examined the primary data for tax manager qualities and machiavellian ethics obtained from 103 tax managers working in manufacturing industry firms at IDX and secondary data from financial statements for tax avoidance. There are 10 tax avoidance indicators used as a proxy. This study gives results that the quality of tax managers have a significant positive effect on Machiavellian ethics. However, machiavellian ethics can not mediate the influence of tax manager quality on tax avoidance.